Science Diplomacy in British Foreign Policy: Theoretical, Institutional, and Organizational Aspects - E. M. Kharitonova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In the context of increasingly tense Russian-British relations the UKRussia Year of Science and Education 2017 offered a window of opportunity to re-establish a constructive dialogue on a number of areas of scientific and technological cooperation, as well as to promote track II diplomacy. Joint activities, held during this year, demonstrated a considerable potential of science diplomacy but revealed substantial differences in the Russian and British views of its objectives and functions. This makes it appropriate to examine the United Kingdom’s experience in science diplomacy and its role in British foreign policy. The first section examines the most common working definition of science diplomacy which differentiates between three categories: ‘science in diplomacy’, ‘science for diplomacy’, and ‘diplomacy for science’. Directly linked to national interests, science diplomacy, can be viewed as a source of ‘soft power’, as an effective conflict prevention and resolution mechanism or as an element of the global governance system. Such multidimensionality of science diplomacy is generally typical of the UK as well. The second section thoroughly examines the development of the discourse on science diplomacy in the British official documents and national science and technology development strategies. The author identifies a fundamental continuity in defining objectives and functions of science diplomacy in the policies of all the Cabinets over the last two decades. Finally, this paper examines organizational and institutional features of science diplomacy in the UK and the activities of the key governmental and non-governmental institutions, societies and organizations engaged in science diplomacy. The conclusion is drawn that British science diplomacy is closely connected with the Kingdom’s key foreign policy objectives and priorities and organically complements more conventional instruments. Moreover, science diplomacy has become all the more important in the light of Brexit..